Economic and employment growth in Germany: The sectoral elements of Verdoorn's Law with regional data - Jens Oelgemöller (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2013)
A major aspect of employment growth is discussed in relation to economic growth. This paper deals with the question as to whether the relationship between economic and employment growth, subsumed under the idiom Verdoorn's Law, holds true at the sectoral level. For this reason, the German labor market is divided into regional functionally delineated labor markets. The employees are differentiated into sectoral affiliation, education, national status and part-time employment. The economy is split into six sectors. The labor demand function is derived from the cost-function of companies, and factor prices (interest rates and wages) are considered. It is evident that the construction sector still has intense connections to the labor market concerning output changes. This cannot be verified in the finance, insurance and service sector. Part-time work increased during the economic crisis. The elasticity to factor-prices holds true for most types of employment. It is found that, regional labor market performance is directly linked to industrial structure. The fixed an random-effects estimations used here deliver satisfying results to most investigations. However, some concerns about the results regarding characteristics of employees remain.
Keywords: J21; J23; O11; R11; 330; Verdoorn; sectoral growth; regional growth; employment elasticity